Successful Roma: from Historically Inherited Biases to Modern Identity - Tilkidjiev, Nikolai; Milenkova, Valentina; Nedelcheva, Tanya; Petkova, Kamelia; Hristova, Svetlana; Mileva, Natasha (Calitatea Vieții, 2010)
This is a presentation of a research project trying to explore the topic of successful Roma in Bulgaria. The subject of successful Roma did not constitute so far, the topic of dedicated research. While some partial studies might address the issue of Roma elites, most of the research concentrated on Roma as a social problem and the subsequent policies. The project described here looks at the life courses of successful Roma, researches the mechanisms (educational, family, professional, informal) which have been a part of the process of individual development and the formation of a national identity among the Roma, analyses the success of Roma in concrete activities and fields of social life and also aims to formulate effective policies for optimizing the participation of successful Roma in the process of the formation of national identity.